Combining natural deep eutectic solvent and microwave irradiation towards the eco-friendly and optimized extraction of bioactive phenolics from Eugenia uniflora L. - Souza, Otávio Aguiar [UNESP]; Ramalhão, Vitória Giovanna da Silva [UNESP]; Trentin, Lucas de Melo [UNESP]; Funari, Cristiano Soleo [UNESP]; Carneiro, Renato Lajarim; Bolzani, Vanderlan da Silva [UNESP]; Rinaldo, Daniel [UNESP] (Elsevier, 2022)
To design a green chemistry future, the development of new protocols for standardization of phytomedicines should consider both traditional and environmental parameters. In the present study, we developed a new natural deep eutectic solvent (NADES)-based microwave-assisted extraction (MAE) of phenolics from leaves of Eugenia uniflora L. This species is used in folk medicine and included in the list of potential plants for phytomedicine production by the Brazilian Health System. Both efficiency of extraction and environmental impact were considered throughout the development, as assessed by three complementary multiparameter metrics (HPLC Environmental Assessment Tool, Analytical Eco-Scale, and Green Analytical Procedure Index). Five food-compatible NADES were initially screened, and choline chloride:lactic acid 1:3 (mol/mol) solubilized in 20% of H2O (wt/wt) obtained the highest extractability of phenolics. Then, a heuristic multivariate optimization of the extraction conditions (plant/NADES ratio, irradiation time, and extraction temperature) was developed by a Central Composite Design with untargeted-targeted purposes. The integrated use of MAE, NADES, and Design of Experiments (DoE) enabled us to obtain a ready-to-use polyphenolic extract from E. uniflora that did not require additional purification steps and employed a more sustainable extraction than other ones previously published in the literature using volatile organic solvents as extraction media. Finally, a comprehensive evaluation demonstrated that this approach has the potential to be applied to other species as an eco-friendly and rational strategy to extract phenolics from plants to search for new active extracts or compounds, and even to the valorization of agro-food residues. The approach also presents a competitive potential over other green methodologies to extract phenolics.
Keywords: Brazilian biodiversity; Green chemistry; Microwave-assisted extraction; Natural deep eutectic solvents; Phenolics